Genetic Variants in Caveolin-1 and RhoA/ROCK1 Are Associated with Clear Cell Renal Cell Carcinoma Risk in a Chinese Population - Zhao, Ruizhe; Liu, Kang; Huang, Zhengkai; Wang, Jun; Pan, Yongsheng; Huang, Yuan; Deng, Xiaheng; Liu, Jinliang; Qin, Chao; Cheng, Gong; Hua, Lixin; Li, Jie; et al. (PloS one, 2015)
The RhoA/ROCK pathway and Caveolin-1 (Cav-1) participate in the process of tumorigenesis in numerous types of cancer. Up-regulation of RhoA/ROCK and Cav-1 expression is considered to be associated with the development and progression of clear cell renal cell carcinoma (ccRCC). We investigated the association between genetic variations of RhoA/ROCK and Cav-1 and the risk of ccRCC in the Chinese population. Between May 2004 and March 2014, a total of 1,248 clear cell renal cell carcinoma cases and 1,440 cancer-free controls were enrolled in this hospital-based case-control study. Nine SNPs in RhoA/ROCK and Cav-1 were genotyped using the TaqMan assay. We found two SNPs (Cav-1 rs1049334 and ROCK1 rs35996865) were significantly associated with the increasing risk of ccRCC (P = 0.002 and P < 0.001 respectively). The analysis of combined risk alleles revealed that patients with 2-4 risk alleles showed a more remarkable growth of ccRCC risk than the patients with 0-1 risk alleles(OR = 1.66, 95%CI = 1.31-2.11, P < 0.001). Younger subjects (P = 0.001, OR = 1.83, 95%CI = 1.30-2.57), higher weight subjects (P = 0.001, OR = 1.76, 95%CI = 1.25-2.47), female subjects (P = 0.007, OR = 1.75, 95% CI = 1.17-2.62), nonsmokers (P < 0.001, OR = 1.67, 95%CI = 1.26-2.23), drinkers (P = 0.025, OR = 1.75, 95% CI = 1.07-2.85), subjects with hypertension (P = 0.025, OR = 1.75, 95% CI = 1.07-2.85) and diabetes (P = 0.026, OR = 4.31, 95% CI = 1.19-15.62) showed a stronger association between the combined risk alleles and the risk of ccRCC by using the stratification analysis. Furthermore, we observed higher Cav-1 mRNA levels in the presence of the rs1049334 A allele in normal renal tissues. Our results indicate that the two SNPs (Cav-1 rs1049334 and ROCK1 rs35996865) and genotypes with a combination of 2-4 risk alleles were associated with the risk of ccRCC. The functional SNP rs1049334 may affect the risk of ccRCC by altering the expression of Cav-1 and the relevance between the risk effects and the functional impact of this polymorphism needs further validation.